Arbitration in the digital age : the brave new world of arbitration - Piers, Maud; Aschauer, Christian (Cambridge : Cambridge University Press, 2018)
Arbitration in the Digital Age analyses how technology can be efficiently and legitimately used to further sound arbitration proceedings. The contributions, from a variety of arbitration scholars, report on current developments, predict future trends, and assesses their impact from a practical, legal, and technical point of view. The book also discusses the relationship between arbitration and the Internet and analyses how social media can affect arbitrators and counsel's behaviour. Furthermore, it analyses the validity of electronic arbitration and awards, as well as Online Arbitration (OArb). The volume establishes, on a very practical level, how technology could be used by arbitration institutions, arbitrators, parties to an arbitration and counsel. This book will be of special interest to arbitrators and lawyers involved in international commercial arbitration.
Title from publisher's bibliographic system (viewed on 19 Jan 2018).
Keywords: Arbitration and award -- Automation; Dispute resolution (Law); Online dispute resolution